Fabrication of low-density carbon-bonded carbon fiber composites with an Hf-based coating for high temperature applications. Issue 34 (24th May 2018) - Xu, Lin; Yang, Wenbing; Fan, Zhen; Li, Xingchao; Li, Wei; Song, Yongzhong; Feng, Zhihai; Zhang, Dahai
Abstract : A novel low-density CBCF composite with an Hf-based coating was designed and prepared, which exhibited a good ablation resistance at the maximum temperature range of 1616–2037 °C for 300 s. Abstract : A novel Hf-based anti-oxidation coating has been prepared on the surface of low-density carbon-bonded carbon fiber composites (CBCFs). The coating exhibits a gradient transition structure, with mainly HfB2, Hf2 Si and SiC ceramics. Oxyacetylene torch testing has been utilized to evaluate the ablation resistance under the condition ranging from 1.6 MW m −2 to 2.2 MW m −2 for 300 s. The experimental results show that the as-prepared Hf-based coating can effectively protect CBCFs under high-temperature oxidation conditions. The surface maximum temperature can reach 1616–2037 °C, and the mass ablation rates vary from −3.5 × 10 −5 g s −1 cm −2 to 1.5 × 10 −5 g s −1 cm −2 . The formation of a dense SiO2 glass layer embedded with HfO2 grains or particle accumulation in the HfO2 layer is responsible for the good ablation resistance.